ANALISIS KESENJANGAN INVESTASI ASING (PMA) DI PROVINSI SULAWESI UTARA: Sebuah Evaluasi Kebijakan Pemekaran Wilayah - Yuliadi, Imamudin (Jurnal Ekonomi & Studi Pembangunan, 2009)
This research aims to know foreign and domestic investment growth among provinces in Indonesia, to identify how many foreign and domestic investment disparity between the provinces in Indonesia, and what factors cause these differences. The research method used is descriptive analysis, trend analysis, regression analysis of foreign and domestic investment disparity between provinces in Indonesia. This research included aspects of regional expansion policy as one of the variables. This research also considered the implications for the possible emergence of an investment gap foreign investment/domestic investment in the area. The results of this research imply that the impact of expansion policy of the province of Gorontalo from North Sulawesi province within short term relatively have not shown significant influence but in the medium and long term have a significant influence on foreign investment gap in the economic context in Eastern Indonesia. The conclusion of this research is that there are disparities issue of foreign investment in North Sulawesi. Disparity investment is also caused by disparity economic infrastructure among region in Indonesia.